Role of chemotherapy in the management of locally advanced carcinoma cervix - Firdaus, Huma; Husain, Ayanat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was undertaken to evaluate role of chemotherapy in the management of locally advanced carcinoma cervix in J.N. Medical College Hospital, A.M.U. Aligarh. Methods: A total of 50 cases were studied. 25 cases received radiotherapy alone or surgery followed by radiotherapy. In remaining 25 cases, 18 patients received neoadjuvant chemotherapy followed by surgery or radiotherapy where as seven patients out of 25 received concurrent chemo-radiation. SPSS software was used for data analysis. Results: Mean age of patient was 51.5 years. Majority of patients (60%) were in FIGO clinical stage IIB followed by stage IIIB (20%), stage IVA (12%) and stage IIA (8%). Out of 25 patients receiving chemotherapy, 68% showed CR whereas 20% showed PR, 4% showed minimal response and 8%showed PD while on chemotherapy. In radiotherapy group, CR was found in 56% and PR in 36% of cases. 8% of patients showed PD while on radiotherapy. Patients with stage IIB disease showed best response with CR in 70% and PR in 16.66% cases. 6.66% of patients showed SD and 6.66% showed PD while on therapy. 55.55% of patients with SCC showed CR and 33.33% showed PR. In adenocarcinoma, CR was seen in 100% cases. In adenosquamous carcinoma, 66.66% showed CR whereas 33.33% showed PR. 61.9% of well differentiated carcinoma showed CR and 28.57% showed PR. 4.76% showed SD and 4.76% showed PD. 58.33% of moderately differentiated carcinoma showed CR, 37.5% showed PR and 4.17% showed SD. 20% of poorly differentiated carcinoma showed CR, 60% showed PR and PD was seen in 20%cases. Patients with bulkly tumours in present study, irrespective of their response to chemotherapy, appeared to have worse prognosis than patients with more advanced pelvic disease. These findings suggest that the biology of bulky stage lb, IIa & IIb disease may be more aggressive than that of more extensive locally advanced disease. Conclusions: Chemotherapy can be considered as an adjuvant to available modalities of treatment, like surgery or radiotherapy, to improve the overall survival of cancer cervix patients.